Heavy metal concentrations in ceiling fan and roadside car park dust collected from residential colleges in Universiti Putra Malaysia, Serdang, Selangor - Yap, Chee Kong; Chew, W. Y.; Tan, Soon Guan (Universiti Putra Malaysia Press, 2012)
In this study, dust samples were collected from 4 residential colleges (K2, K5, KOSAS and K10) in UniversitiPutra Malaysia (UPM) Serdang, Selangor. The samples were collected from ceiling fans and car parksroadside dust. Sand dust on top of the car park cover were collected using polyethylene brush, tray and keptin a polyethylene bag. Dust from ceiling fan on the first floor was collected and put into a polyethylene bag.The dust samples collected were analysed for the concentrations of Cd, Cu, Fe, Ni and Zn. It was found thatK5 [Cu (62.94 ± 0.77 µg/g dw), Fe (1802.40 ± 9.81 µg/g dw), and Zn (253.34 ± 22.76 µg/g dw) of car parkdust; Zn (997.20 ± 16.10 µg/g dw) (of ceiling fan dust] and K10 [Ni (26.88 ± 1.84 µg/g dw) and Zn (199.77± 6.64 µg/g dw) of car park dust; Cu (468.55 ± 3.67 µg/g dw), Ni (83.96 ± 0.75 µg/g dw), and Fe (3131.58 ±27.01 µg/g dw) of ceiling fan dust] exhibited elevated concentrations of heavy metals that might be related tovehicular activities as compared to K2 and KOSAS. In general, ceiling fan dust had significantly (P< 0.05)higher concentrations of heavy metals than the car park dust. In comparison to other reported studies in theliterature, the maximum levels of Ni and Cu were comparable or higher than those reported for major cities inthe world. Hence, more monitoring studies should be conducted in the future to check for metal contaminationin the dust, as this can serve as an atmospheric indicator of heavy metal pollution.